2021
DOI: 10.3390/su13041888
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Multiple Large Shareholders on Banks’ Profitability and Risk

Abstract: The wide-ranging academic literature on corporate governance in the banking sector includes only a few studies on bank ownership and, specifically, on the comparative power of shareholders within the corporate structure. This paper reports an investigation into the presence of multiple large shareholders and their influence on profitability and risk in the long-term, considering a sample of 697 U.S. and European listed commercial banks from 2008 to 2018. It was found that the number of large and institutional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 82 publications
(109 reference statements)
1
6
0
Order By: Relevance
“…Therefore, if the monitoring effect of share ownership by institutional investors occurs, it is expected to have a positive impact on corporate performance. The previous studies show that institutional ownership positively affects profitability (Soana et al, 2021;Sakawa & Watanabel, 2020;Amanda et al, 2020;Nurkhin et al, 2017;Ozili & Uadiale, 2017). Thus, the proposed hypothesis is: H3: Institutional ownership affects the profitability of the banking sector listed on the Indonesia Stock Exchange Working Capital Management and Profitability Working capital management (WCM) is short-term financial management used to control and manage current assets and liabilities that involve short-term cash flows in the company's operating cycle (Seth et al, 2019).…”
Section: Literature Review Intellectual Capital and Profitabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if the monitoring effect of share ownership by institutional investors occurs, it is expected to have a positive impact on corporate performance. The previous studies show that institutional ownership positively affects profitability (Soana et al, 2021;Sakawa & Watanabel, 2020;Amanda et al, 2020;Nurkhin et al, 2017;Ozili & Uadiale, 2017). Thus, the proposed hypothesis is: H3: Institutional ownership affects the profitability of the banking sector listed on the Indonesia Stock Exchange Working Capital Management and Profitability Working capital management (WCM) is short-term financial management used to control and manage current assets and liabilities that involve short-term cash flows in the company's operating cycle (Seth et al, 2019).…”
Section: Literature Review Intellectual Capital and Profitabilitymentioning
confidence: 99%
“…Then, Jihadi et al (2021), Chen et al (2019), Aggarwal &Padhan (2017), andDalci (2018) find that financial leverage has a positive effect on profitability. Furthermore, research conducted by Soana et al (2021), Sakawa & Watanabel (2020), Amanda et al (2020), Nurkhin et al (2017), andOzili &Uadiale (2017) show that institutional ownership positively affects profitability. Several research results also agree that WCM affects company profitability (Gonçalves et al, 2018;Godswill et al, 2018;Morshed, 2020;Pham et al, 2020;Senan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Capital adequacy indicates the level of banks’ compliance with regulations of the minimum capital reserve amount. The capital structure concentration for any bank is highly important, as shown in [ 24 ], whose findings revealed that the number of large and institutional shareholders of banks has a positive effect only on profitability, not on risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other scholars have explored banks’ management quality through the implementation of best corporate governance and social responsibility practices [ 24 , 51 53 ]. [ 51 ] applied different corporate governance practices in banks (i.e., female independent directors, CEO duality, and CEO shareholding) and found that bank financial performance was positively affected by these practices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Activity ratios show how quickly an enterprise pays its debts and collects receivables as well as how effectively it manages its inventory. Profitability indicators express the relationship between operating profits, net sales revenues, total assets, and equity [47,70,71]. The profitability of forest districts is primarily determined by their costs (optimized by the State Forests management) and revenues, which depend on natural conditions (volume and quality of timber) and market demand.…”
Section: Ratio Analysis As a Tool For Evaluating The Financial Performance Of Forest Districtsmentioning
confidence: 99%